Conversa na sombra das palavras - Camelatto, Patricia (2011)
The conversations, letters and images that compose this work are devices created to produce conditions for experimentation, in order to get detached from the policy of producing concepts, which is understood as a revelation of a supposed truth. The function of writing is clinical, driven by a desire of experimenting, expanding and creating new criteria for navigation and intervention in existence. The script passes through areas of epidermal interests that are interconnected. This is done to experience connections when released